2021
DOI: 10.2217/imt-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Clinical Trials on Immunotherapy for Human Leishmaniases: a Systematic Review and Meta-Analysis

Abstract: Aim: Current treatments for leishmaniases are not satisfactory, thus alternatives are needed. We searched for clinical trials with immunotherapeutic approaches for patients with leishmaniasis. Materials & methods: Out of 205 articles, 24 clinical trials were selected, and eight submitted to meta-analysis. Results: A reduction in healing time was observed in patients with tegumentary leishmaniasis treated with pentavalent antimony plus granulocyte-macrophage colony-stimulating factor, and therapeutic vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…A significant in vivo leishmanicidal effect that induced subsequent resolution of lesions was evidenced both with Glucantime ® , the agent used to successfully treat the CL patient from whom the UA-946 L(V)p was isolated, and with Miltefosine, which has been increasingly used to treat CL in the New World ( Pinart et al, 2020 ). Likewise, since host-directed immunotherapeutic interventions have been used to treat leishmaniasis ( Mota et al, 2021 ) and are gaining special attention ( Novais et al, 2021 ), we also confirmed that low dose of the TLR9 agonist CpG protected mice clinically and parasitologically from L(V)p CL when co-delivered with the challenge or when used as an adjuvant of total L(V)p antigen in a vaccination setting ( Zimmermann et al, 1998 , 2008 ; Raman et al, 2012 ). Moreover, the model allowed us to identify a protective 28–30 kDa L(V)p subproteome (termed F9) via forward vaccinology and confirm that F9 induces a shift toward a Th1 response.…”
Section: Discussionsupporting
confidence: 78%
“…A significant in vivo leishmanicidal effect that induced subsequent resolution of lesions was evidenced both with Glucantime ® , the agent used to successfully treat the CL patient from whom the UA-946 L(V)p was isolated, and with Miltefosine, which has been increasingly used to treat CL in the New World ( Pinart et al, 2020 ). Likewise, since host-directed immunotherapeutic interventions have been used to treat leishmaniasis ( Mota et al, 2021 ) and are gaining special attention ( Novais et al, 2021 ), we also confirmed that low dose of the TLR9 agonist CpG protected mice clinically and parasitologically from L(V)p CL when co-delivered with the challenge or when used as an adjuvant of total L(V)p antigen in a vaccination setting ( Zimmermann et al, 1998 , 2008 ; Raman et al, 2012 ). Moreover, the model allowed us to identify a protective 28–30 kDa L(V)p subproteome (termed F9) via forward vaccinology and confirm that F9 induces a shift toward a Th1 response.…”
Section: Discussionsupporting
confidence: 78%
“…The toxicity and mortality caused by these drugs justify the recommendation to administer liposomal amphotericin B over pentavalent antimonials in individuals with VL and HIV (35). The combination of pentavalent antimonials with recombinant interferon-gamma showed cure rates ranging from 69% to 100%, but further studies are needed to confirm this combination is superior to antimonials alone (39). On the other hand, the combination of pentavalent antimonials with paromomycin, evaluated in Ethiopia, produced a therapeutic success of 90.1% (37).…”
Section: Treatmentmentioning
confidence: 99%
“…Another approach is to use combined therapy, associating immunotherapeutics with classic drugs to improve patient outcomes [26,27]. A few clinical trials, conducted in the last three decades, have shown positive results, with combined immunotherapy reducing the healing time for patients, but more studies are needed before these combinations receive market approval [27].…”
Section: Clinical Forms and Treatmentmentioning
confidence: 99%